First-in-Human Randomized, Controlled Trial of Mosaic HIV-1 Immunogens Delivered via a Modified Vaccinia Ankara Vector. (13th April 2018) - Baden, Lindsey R; Walsh, Stephen R; Seaman, Michael S; Cohen, Yehuda Z; Johnson, Jennifer A; Licona, J Humberto; Filter, Rachel D; Kleinjan, Jane A; Gothing, Jon A; Jennings, Julia; Peter, Lauren; Nkolola, Joseph; et al.
Abstract : The genetic diversity of human immunodeficiency virus type 1 (HIV-1) is a significant challenge to developing a prophylactic vaccine. One strategy to increase cellular immune responses is the use of computationally derived mosaic immunogens. In this first-in-human assessment, multiclade HIV-1–specific immune responses were elicited. Abstract: Background: Mosaic immunogens are bioinformatically engineered human immunodeficiency virus type 1 (HIV-1) sequences designed to elicit clade-independent coverage against globally circulating HIV-1 strains. Methods: This phase 1, double-blinded, randomized, placebo-controlled trial enrolled healthy HIV-uninfected adults who received 2 doses of a modified vaccinia Ankara (MVA)–vectored HIV-1 bivalent mosaic immunogen vaccine or placebo on days 0 and 84. Two groups were enrolled: those who were HIV-1 vaccine naive (n = 15) and those who had received an HIV-1 vaccine (Ad26.ENVA.01) 4–6 years earlier (n = 10). We performed prespecified blinded cellular and humoral immunogenicity analyses at days 0, 14, 28, 84, 98, 112, 168, 270, and 365. Results: All 50 planned vaccinations were administered. Vaccination was safe and generally well tolerated. No vaccine-related serious adverse events occurred. Both cellular and humoral cross-clade immune responses were elicited after 1 or 2 vaccinations in all participants in the HIV-1 vaccine–naive group. Env-specific responses were induced after a single immunization in nearly all subjects who had previously received the prototype Ad26.ENVA.01 vaccine. Conclusions: No safety concerns were identified, and multiclade HIV-1–specific immune responses were elicited. Clinical Trials Registration: NCT02218125.